Sistem Pendukung Keputusan Dalam Menentukan Siswa Terbaik Menggunakan Metode Simple Additive Weighting (SAW) - Utami, Rida (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
In this study, the authors aim to design and build a decision support system at Medan Putri Private Junior High School. The method used by the author is the Simple Additive Weighting (SAW) method. There are five criteria used by the author, namely good ethics, active in class, the highest report card value, and attendance. The use of a Decision Support System (DSS) is expected to help the decisions made in choosing and determining who is the best student, considering that so far, no particular method has been used in selecting students so that sometimes decisions are deemed less objective and not on target. In this study, a case will be appointed, namely looking for the best alternative based on predetermined criteria using the Simple Additive Weighting (SAW) method. The research was conducted by finding the weight value for each attribute; then, a ranking process was carried out, which would determine the optimal alternative, namely the best student.